2009
DOI: 10.1016/j.ejvs.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis Comparing Open Surgical and Endovascular Treatment of Atherosclerotic Renal Artery Stenosis

Abstract: This data shows a marked and durable clinical benefit for surgery. These findings question the endovascular predominance in intervention in ARAS and highlight the need for a carefully designed prospective randomised comparison to define the roles of endovascular and surgical renal revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The analytic sensitivity was <5.0 pg ml À1 , with a measurable range of 0e5000 pg ml À1 . As previously described, age-and genderspecific median levels (25th and 75th percentiles) of plasma BNP using the same Biosite assay in 767 normal subjects in sinus rhythmus without cardiovascular disease or cardiac dysfunction were 27 (15, 43) pg ml À1 and 11 (5,20) pg ml À1 for women and men of 55e64 years of age, and 29 (19, 52) pg ml À1 and 18 (7, 37) pg ml À1 for women and men of 65e74 years of age, respectively. 15 The laboratory technician who measured BNP was blinded to patient information.…”
Section: Blood Sampling and Laboratory Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…The analytic sensitivity was <5.0 pg ml À1 , with a measurable range of 0e5000 pg ml À1 . As previously described, age-and genderspecific median levels (25th and 75th percentiles) of plasma BNP using the same Biosite assay in 767 normal subjects in sinus rhythmus without cardiovascular disease or cardiac dysfunction were 27 (15, 43) pg ml À1 and 11 (5,20) pg ml À1 for women and men of 55e64 years of age, and 29 (19, 52) pg ml À1 and 18 (7, 37) pg ml À1 for women and men of 65e74 years of age, respectively. 15 The laboratory technician who measured BNP was blinded to patient information.…”
Section: Blood Sampling and Laboratory Methodsmentioning
confidence: 75%
“…Second, in this prospective, non-randomised cohort study, all of the patients received percutaneous revascularisation of RAS without inclusion of any control group. Therefore, our results may not be applicable to patients undergoing surgical correction of RAS, 5 and we cannot preclude that factors other than RAS may have contributed to the elevation of BNP. However, median levels of BNP in our cohort with RAS were elevated compared with a previously published healthy control group and a patient cohort of severe essential hypertension.…”
Section: Study Limitationsmentioning
confidence: 91%
“…A meta-analysis study, by Abela et al, 15 demonstrated that, for suitable patients, the surgical revascularization could be a better option for improving renal function and adequate control of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies show that endovascular revascularization is effective in high-risk patients, such as those with acutely deteriorating renal function and uncontrolled hypertension [10,11]. Other authors showed that endovascular revascularization in addition to medical therapy lowered requirements for antihypertensive medications without an improvement in kidney function compared to medical therapy alone [12,13].…”
Section: Discussionmentioning
confidence: 99%